Advances in the management of liver and biliary tumors. Issue 5 (10th September 2022) - Jarnagin, William R.; D'Angelica, Michael I.
Abstract: Over the past 50 years, the management of liver and biliary tumors has evolved significantly. Initially considered highly morbid and lethal, resection is now the treatment of choice for a significant proportion of patients with malignant and benign hepatobiliary disease. Improved operative/anesthetic techniques, use of parenchymal‐sparing approaches, better patient selection for surgery, effective liver‐directed therapies, and new insights into tumor biology are significant contributors to our transformed approach to hepatobiliary neoplasms.